STRUKTUR PEREKONOMIAN INDONESIA DAN PENGARUHNYA PADA INDUSTRI KAYU MENTAH - Socia Prihawantoro; Budy P. Resosudarmo (Journal of Indonesian Economy and Business (JIEB), 1999)
It is commonly known, in Indonesia, that a high growth rate of log productioninduces a high rate of deforestation. Hence, to reduce the rate of deforestation, it isnecessary for Indonesia to decrease its log production.Implementing policies only in the logging sector might not be enough to beable to reduce the log production. It is suspected that many other sectors in theeconomy give high pressures to the logging sector to produce more. This study,implementing a Social Accounting Matrix (SAM), analyze the Indonesian economicstructure to determine which sectors do actually give high pressures to the loggingsector to produce more.